Literacy practice – Providing reading and writing in the early years of elementary school (Research, Society and Development, 2022)
This article focuses on the theme of teaching-learning reading and writing in the Early Years of Elementary School. Its main goal is to reflect on teaching practice and present a didactic suggestion for reading and writing. Based on Geraldi (2012), Soares (2020), Lopes-Rossi (2008), and in the dialogic approach (BAKHTIN, 2011), this research discusses how to develop the reading practice taking into account its goals as well as how writing is comprehended from discourse and genre-based perspective. This work made use of a state-of-the-art survey and a theoretical-oriented bibliographical study as methodological procedures focusing on teaching practice. Preliminary results point that teachers need to be trained and have access to research tools. At the same time, teachers need to be engaged in extension activities, research groups, and scientific events which demand the ongoing training of these professionals to give a new meaning to their pedagogical practice.